2019
DOI: 10.1200/jgo.19.00118
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Education of Patients With Cancer in a Low- and Middle-Income Country: A Quality Improvement Project Using the Cancer and You Booklet

Abstract: PURPOSE The Butaro Cancer Centre of Excellence is the first comprehensive referral cancer center in Rwanda and at its inception did not have a standardized patient education program. Partners in Health/Inshuti Mu Buzima and the Rwandan Ministry of Health conducted a quality improvement project to increase patient knowledge by implementing a standardized oncology education program using picture-based and culturally appropriate materials designed for patients with cancer in low- and middle-income countries. METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…The acceptability of the booklet in this study was similar to the implementation experience in Rwanda and the prior pilot in Haiti. 4 , 5 Comparing the Haitian and Nigerian studies highlights a key difference in education level: 88% of the Nigerian sample (with a known education level) had a secondary education level or higher in comparison to only 40% (8 of 20) in the Haiti study. The pretest score average was about 50% in Haiti.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The acceptability of the booklet in this study was similar to the implementation experience in Rwanda and the prior pilot in Haiti. 4 , 5 Comparing the Haitian and Nigerian studies highlights a key difference in education level: 88% of the Nigerian sample (with a known education level) had a secondary education level or higher in comparison to only 40% (8 of 20) in the Haiti study. The pretest score average was about 50% in Haiti.…”
Section: Discussionmentioning
confidence: 99%
“…When the booklet is paired with nurses teaching patients, patient understanding appears to be reasonable. 4 The social desirability response bias could have influenced patient's answers. 35 Finally, the qualitative analysis is limited by the way responses were recorded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that the level of education did not significantly affect the patient's psychological status. Educated women might be more aware of cancer as well as be more able to gain the information needed to cope with their condition and be more satisfied with the treatment [ 39 ]. On the other hand, educated patients might feel overstressed and start to expect the worst the more they know about their cancer and use rumination and self-criticism to cope with cancer resulting in anxiety and depression [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Information on the benefits and risks of ICI is critical for patients who have both an autoimmune disease and cancer and who are candidates for ICI treatment. Patient education can facilitate patient-provider communication, improve the tracking and reporting of adverse events, and help patients to feel more involved in and satisfied with their care [8,9]. However, educational resources tailored to the informational needs of this patient population have not yet been developed.…”
Section: Introductionmentioning
confidence: 99%